Metastasis of Ewing Sarcoma to the Pancreas: Case Report and Literature Review - Hyma Polimera; Prashanth Moku; Shady Piedra Abusharar; Monali Vasekar; Jayakrishna Chintanaboina (Case Reports in Oncological Medicine)
Ewing sarcoma (ES) is a highly aggressive malignant bone cancer. ES is part of the Ewing sarcoma family of tumors (ESFT), which express characteristic t(11;22) translocation as well as higher levels of CD99. Given that metastasis and tumor burden are significant prognostic factors in patient’s response to treatment, prompt diagnosis is needed to effectively treat ESFT patients. However, the challenges in classifying and characterizing ESFT complicate effective management and treatment of ES. In this report, we present a rare case of ES metastasis to the pancreas. Upon review of the literature, we found 39 cases of ESFT involving the pancreas, but only 3 were metastatic to the pancreas while the remaining cases of ESFT primarily originated from the pancreas. Given the rarity of such metastasis, the positive outcome in our patient’s case may explain the importance of prompt diagnosis in order to initiate appropriate treatment.